KHA‐CARI Guideline recommendations for renal biopsy. Issue 12 (23rd October 2019) - MacGinley, Rob; Champion De Crespigny, Paul J; Gutman, Talia; Lopez‐Vargas, Pamela; Manera, Karine; Menahem, Solomon; Saunders, John; See, Emily; Voss, David; Wong, Jeffrey
SUMMARY AT A GLANCE: This KHA‐CARI Guideline laid down principles for the care of patients undergoing kidney biopsy, and provides management guidelines from with‐holding of antiplatelet and anticoagulant agents, application of desmopressin to postbiopsy bleeding care.